Clinical and economic implications of therapeutic switching of angiotensin receptor blockers to angiotensin-converting enzyme inhibitors: a population-based study. Issue 6 (June 2019) - Kurdi, Amanj I.B.; Elliott, Rachel A.; Chen, Li-Chia
Abstract : Objective: To evaluate the clinical and cost impact of switching angiotensin receptor blockers (ARBs) to angiotensin-converting enzyme inhibitors (ACEIs) in patients with hypertension. Methods: This study used the UK Clinical Practice Research Datalink, linking with the Hospital Episode Statistics (April 2006 to March 2012). Adults with hypertension ( n  = 470) were followed from the first ARB prescription date to the switching date (preswitching period); then from the switching date to the date when study ended, patient left the dataset or died (postswitching period). Patients were divided into ACEIs-combined ( n  = 369) and ACEIs-monotherapy ( n  = 101) groups by whether additional antihypertensive drugs were prescribed with ACEIs in the postswitching period. Proportion of days covered (PDC), clinical outcomes and costs were compared between the preswitching and postswitching periods using a multilevel regression. Results: Overall, in the postswitching period, there was a significant increase in the proportion of nonadherence (PDC < 80%) (OR: 2.4; 95% CI: 1.6–3.7), but a significant reduction in mean SBP (mean difference: −2.3; 95 CI: −3.4 to 1.2 mmHg) and mean DBP (mean difference: −1.9; 95% CI: −2.6 to −1.2 mmHg). However, these results were only observed in the ACEIs-combined group. There was no postswitching significant difference in either the incidence of individual or composite hypertension-related complications (OR: 0.9; 95% CI: 0.4–2.0). There was a significant reduction in the overall annual medical cost per patient by £329 (95% CI: −534 to −205). Conclusion: Switching of ARBs to ACEIs monotherapy appeared to be clinically effective and a cost-saving strategy. The observed changes in the ACEIs-combined group are assumed to be related to factors other than the ARBs switching.